A bi-national examination of gender and IT adoption. (4th June 2010) - Joseph, Jimmie L.; Mukhopadhyay, Somnath
Innovation diffusion theory indicates that cultural and economic factors, affect the adoption and diffusion of information technology. This research examines demographic factors for two populations on either side of an international border, to compare IT penetration. A border region was chosen to ensure that differences in technology availability, shipping costs and other factors were minimised. The research found that women had fewer computers at home than men. Further, women born in the USA and living in the USA had fewer computers than either women born in Mexico and living in the USA or women born in Mexico and living in Mexico.